GENOME SEQUENCING OF POTATO LATE BLIGHT PATHOGEN, PHYTOPHTHORA INFESTANS A2 MATING TYPE - Singh, Youvika; Rawal, H C; Sharma, T R; Singh, B P; Shukla, Pradeep K; Sharma, Sanjeev; Patil, V U; Chakrabarti, S K; Rawat, Shashi (Potato Journal, 2017)
Â Â Â